Developing Employer Branding Strategy Based on Design Science Research to Attract Generation Z's Intention to Apply at Company A - Epafradias Sabdanta Kaban; Mone Stepanus Andrias (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Generation Z is increasingly dominating the workforce with unique preferences for work-life balance, sustainability, and personal development. Companies face challenges in designing employer branding strategies that attract this generation's intention to apply. This study employs the Design Science Research (DSR) approach to develop an evidence-based employer branding strategy for Company A. The literature review covers employer branding, intention to apply, and Generation Z characteristics. This research is expected to provide academic contributions and strategic guidelines for companies in attracting and retaining young talent.